DEVELOPING LEADERSHIP COMPETENCE IN YOUNG LANGUAGE LEARNERS THROUGH INTERACTIVE METHODS - Risvayeva Charos Zaydilla qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  examines  the  importance  of  developing  leadership competence among young language learners through interactive teaching methods. In modern education, language learning is no longer limited to acquiring grammatical knowledge  and  vocabulary.  It  also  involves  the  development  of  communication, collaboration, critical thinking, and leadership abilities. Interactive methods such as group  discussions,  role  plays,  debates,  project-based  learning,  and  problem-solving activities create opportunities for learners to demonstrate initiative, responsibility, and teamwork.  The  study  highlights  how  these  methods  contribute  to  building  self-confidence, decision-making skills, and social interaction among students.